Small Non-coding RNA Expression and Vertebrate Anoxia Tolerance - Riggs, Claire L.; Summers, Amanda; Warren, Daniel E.; Nilsson, Göran E.; Lefevre, Sjannie; Dowd, W. W.; Milton, Sarah; Podrabsky, Jason E. (Frontiers in Genetics, 2018)
Background: Extreme anoxia tolerance requires a metabolic depression whose modulation could involve small non-coding RNAs (small ncRNAs), which are specific, rapid, and reversible regulators of gene expression. A previous study of sncRNA expression in embryos of the annual killifish Austrofundulus limnaeus, the most anoxia-tolerant vertebrate known, revealed a specific expression pattern of sncRNAs that could play important roles in anoxia tolerance. Here, we conduct a comparative study on the presence and expression of small ncRNAs in the most anoxia-tolerant representatives of several major vertebrate lineages, to investigate the evolution of and mechanisms supporting extreme anoxia tolerance. The epaulette shark (Hemiscyllium ocellatum), crucian carp (Carassius carassius), western painted turtle (Chrysemys picta bellii), and leopard frog (Rana pipiens) were exposed to anoxia and recovery, and sncRNAs were sequenced from the brain (one of the most anoxia-sensitive tissues) prior to, during, and following exposure to anoxia. Results: Small ncRNA profiles were broadly conserved among species under normoxic conditions, and these expression patterns were largely conserved during exposure to anoxia. In contrast, differentially expressed genes are mostly unique to each species, suggesting that each species may have evolved distinct small ncRNA expression patterns in response to anoxia. Mitochondria-derived small ncRNAs (mitosRNAs) which have a robust response to anoxia in A. limnaeus embryos, were identified in the other anoxia tolerant vertebrates here but did not display a similarly robust response to anoxia. Conclusions: These findings support an overall stabilization of the small ncRNA transcriptome during exposure to anoxic insults, but also suggest that multiple small ncRNA expression pathways may support anoxia tolerance, as no conserved small ncRNA response was identified among the anoxia-tolerant vertebrates studied. This may reflect divergent strategies to achieve the same endpoint: anoxia tolerance. However, it may also indicate that there are multiple cellular pathways that can trigger the same cellular and physiological survival processes, including hypometabolism.